India's development and public policy - Nagel, Stuart S., 1934- (Policy studies organization (Series) (Aldershot, England), 2000)
"This book analyzes India's development and public policy from the perspectives of five major fields of public policy. They consist of (1) economic policy, including public policy toward industrial development, (2) social policy, including religion, education and women's rights, (3) environmental policy, including possible conflict with economic development, (4) science-technology policy, including agricultural development, information technology and administering the electronics industry, and (5) political reform, including local government and general elections."--Jacket.